Evaluation of affinity matured Affibody molecules for imaging of the immune checkpoint protein B7-H3; Nuclear Medicine and Biology; Vol. 124-125 - Oroujeni M. Maryam; Bezverkhniaia E. A. Ekaterina Aleksandrovna; Xu Tianqi; Liu Yongsheng; Plotnikov E. V. Evgeny Vladimirovich; Klint S. Susanne; Ryer E. Eva; Karlberg I. Ida; Orlova A. M. Anna Markovna; Frejd F. Y. Fredrik; Tolmachev V. M. Vladimir Maksimilianovich (2023, 2023)
Title screen